Using Drosophila nephrocytes in genetic kidney disease. - Helmstädter, M.; Simons, M. (Cell and Tissue Research, 2017)
Renal diseases are a growing health burden, and innovative models to study their pathomechanisms are greatly needed. Here, we highlight how the fruit fly Drosophila melanogaster can be used to model kidney diseases. We focus on the nephrocyte that has recently been shown to exhibit podocyte and proximal tubular cell features. These cells can be manipulated with precise genetic tools to dissect filtration and reabsorption mechanisms. Thus, they represent a novel and easy-to-use alternative in experimental nephrology.